Remembrance tourism in former multicultural Galicia: The revival of the Polish–Ukrainian borderlands. (July 2016) - Bechtel, Delphine
The historical region of Galicia was appropriated successively by the Habsburg Imperium, Independent Poland, the USSR, Hitler Germany, and Communist Poland and the USSR. It is presently divided in to two by the border between Poland and Ukraine, the EU and the belt of post-Soviet states. Its multicultural past has been eradicated through genocide, ethnic cleansing, and deportations by Hitler and Stalin as well as various interethnic conflicts between Polish and Ukrainian nationalists. From 1989 on, pilgrims, survivors, root tourists, and also religious, political, and community activists have started to rediscover it. Poles, Ukrainians, Jews, as well as Russian and Western travelers cross the borders to remember their childhood places, the locus of their deportation or survival, or the cradle of the family history, or just a province lost. Their expectations are partly met, or sometimes ignored, by municipal and regional authorities, travel agencies, private businesses, and locals, who all contribute to form a network of touristic infrastructures. The memory of WW2 and of the subsequent deportations looms large in the personal agendas of tourists and community activists. However, Poland and Ukraine envision local, historical, and identity tourism in the region variously. While Western Ukraine tries to convey a strongly nationalistic and monoethnic image of the region, Poland, under the influence of EU guidelines and subsidies, has opened to a more multicultural and postmodern concept. Transnational tourism across the border participates in the reassertion of conflicting national identities.